The effect of application of "Tentang Kita" module on the knowledge, attitude and motivation of peer educators at PIK-R IKIP Siliwangi, Cimahi City - Fitri Nurhayati; Anisa Kurnia Ramdhini; Siti Nur Endah (Science Midwifery, 2022)
Teenagers who experience reproductive issues frequently get married young, engage in unsafe sexual behavior, and abuse drugs (WHO, 2020). Health education is one method midwives may help people with these issues. A reproductive health module called "Tentang Kita" has been created by BKKBN. This module's segmentative, peer-to-peer, and participatory/interactive features are its benefits. This study's objective was to ascertain how the "Tentang Kita" module's implementation affected the knowledge, attitudes, and motivation of peer educators at PIK-Remaja IKIP Siliwangi. Type of the research are quasi experimental with one group pre test-post test design. The sample of this study were 30 members of PIK-R IKIP Siiwangi. Data collection used questionnaires with intervention using "Tentang Kita" module. Data analysis was done univariate and bivariate with Wilcoxon test. The median knowledge before intervention was 62.5 while the median knowledge after intervention was 96. The median attitude before intervention was 74 while the median attitude value after intervention was 93. The median motivation before intervention is 77 while the median motivation after intervention is 95. Result of this study, there is an effect of the application of "Tentang Kita" module on the knowledge, attitudes and motivation of peer educators at PIK-R IKIP Siliwangi with a p value of 0.000. The use of the "Tentang Kita" module had an impact on peer educators' knowledge, attitudes, and motivation, according to the study's findings. It is advised that several parties, especially adolescents, PIK-R, and health centers as first-level medical facilities, should actively participate in reproductive health issues.